Virtual Histology Analysis of Carotid Atherosclerotic Plaque: Plaque Composition at the Minimum Lumen Site and of the Entire Carotid Plaque. Issue 1 (29th November 2012) - Tsurumi, Arihito; Tsurumi, Yuko; Hososhima, Osamu; Matsubara, Noriaki; Izumi, Takashi; Miyachi, Shigeru
<x xml:space="preserve">Abstract</x> ABSTRACT BACKGROUND Virtual Histology intravascular ultrasound (VH IVUS) volumetric analysis (analysis of the entire plaque responsible for stenosis) has been used for carotid plaque diagnosis. Knowing the carotid plaque characteristics by analyzing the plaque composition only at the minimum lumen site will facilitate plaque diagnosis using VH IVUS. PURPOSE To detect the relationship between the VH IVUS volumetric analysis of the entire plaque responsible for carotid artery stenosis and the VH IVUS cross‐section plaque analysis at the minimum lumen site. METHODS Forty‐eight atherosclerotic cervical carotid stenoses in 45 consecutive patients were included in the study. VH IVUS was obtained during the carotid artery stenting procedure. RESULTS Simple regression analysis revealed that the volumetric proportion of each plaque type correlated significantly with the corresponding plaque‐type area at the minimum lumen site. The adjusted coefficients of determination of the simple regression analyses were .782 (P < .001) for fibrous tissue, .741 (P < .001) for fibrofatty tissue, .864 (P < .001) for dense calcium, and .918 (P < .001) for necrotic core. CONCLUSION The plaque composition at the minimum lumen site represents the volumetric composition of the entire carotid plaque that causes atherosclerotic cervical carotid artery stenosis.